Marjory Stoneman Douglas, voice of the Everglades - Bryant, Jennifer; Raymond, Larry (Frederick, Md. : Twenty-first Century Books, 1992)
Traces the life of the woman who became known as the "Grandmother of the Glades" for her fight to preserve the Florida Everglades against misuse and development.
Includes index.
Elem. School Library Collection
School Library Journal
Book Links (A.L.A.)
6.3
3-6
Keywords: Douglas, Marjory Stoneman -- Juvenile literature; Douglas, Marjory Stoneman; Conservationists -- Florida -- Biography -- Juvenile literature; Everglades (Fla.) -- Juvenile literature; Conservationists; Everglades (Fla.); Douglas, Marjory Stoneman; Conservationists -- Biography; Everglades (Fla.)